Empowering authors in crafting children's literature with artificial intelligence - Peh, Bing Wei (Nanyang Technological University, 2024)
This project explores the integration of Artificial Intelligence (AI) into the process of creating children’s literature, aimed to empower authors with the help of AI to enhance storytelling and engagement. Utilizing AI technologies, including natural language processing and image generation, the system facilitates the generation of narrative content and corresponding illustrations, effectively bridging the gap between traditional storytelling techniques and modern digital capabilities.